Karakteristik Fisik, Kimia, dan Fungsional Buah Terung Belanda (Solanum betaceum) dari Dua Agroekosistem Dataran Tinggi di Sumatera Barat - Rahmi, Rahmi Holinesti; Yusniwati; Anggraini, Tuty; Syukri, Daimon (Pasundan Food Technology Journal (PFTJ), 2025)
Tamarillo (Solanum betaceum) is a highland fruit species endowed with considerable economic significance and functional potential as a natural source of bioactive compounds and pigments. Nevertheless, comprehensive investigations elucidating the interplay between agroecosystem conditions and the morphological, chemical, and functional attributes of this fruit remain scarce in tropical regions. The present study aimed to compare the quality characteristics of tamarillo fruits cultivated under two distinct highland agroecosystems in West Sumatra—Alahan Panjang (Solok) and Bukik Batabuah (Agam). Analyses encompassed assessments of physical, chemical, and functional properties, with data evaluated using independent t-tests (α = 0.05).Tamarillo fruits originating from Alahan Panjang exhibited superior quality attributes, characterized by larger fruit size, firmer texture, enhanced nutritional composition, higher color intensity, stronger antioxidant capacity, and greater antimicrobial activity against Escherichia coli and Staphylococcus aureus. Although fruits from Bukik Batabuah demonstrated comparatively lower performance, the site nonetheless possesses potential as a production area when supported by optimized cultivation and postharvest management practices.These findings underscore the pivotal influence of highland agroecosystem conditions on tamarillo fruit quality and reinforce its value as a natural functional food resource. Furthermore, this research contributes to advancing the United Nations Sustainable Development Goals (SDGs), specifically Goal 2 (Zero Hunger), Goal 3 (Good Health and Well-being), Goal 8 (Decent Work and Economic Growth), and Goal 12 (Responsible Consumption and Production). Keywords: Agroecosystem, Functional Characteristics, Phytochemical Properties, Physical Attributes, Tamarillo (Solanum betaceum).